Developing Digital RF Memories and Transceiver Technologies for Electromagnetic Warfare - Pace, Phillip E. (Artech House, 2022)
This book provides a comprehensive resource and thorough treatment in the latest development of Digital RF Memory (DRFM) technology and their key role in maintaining dominance over the electromagnetic spectrum. Part I discusses the use of advanced technology to design transceivers for spectrum sensing using unmanned systems to dominate the electromagnetic spectrum. Part II uses artificial intelligence and machine learning to enable modern spectrum sensing and detection signal processing for electronic support and electronic attack. Another key contribution is examination of counter-DRFM techniques. DRFM and transceiver design details and examples are provided along with the MATLAB software allowing the reader to construct their own embedded DRFM transceivers for unmanned systems. It examines the design trade-offs in developing multiple, structured, false target synthesis DRFM architectures and aids in developing counter-DRFM techniques and distinguish false target from real ones. Written by an expert in the field, and including MATLAB"!design software, this is the only comprehensive book written on the subject of DRFM
Keywords: Digital communications.; Radio -- Transmitter-receivers.; Electromagnetic waves.; Electronics in military engineering.; elektronické knihy; electronic books